In Situ Probing of Ion Ordering at an Electrified Ionic Liquid/Au Interface. Issue 27 (12th May 2017) - Sitaputra, Wattaka; Stacchiola, Dario; Wishart, James F.; Wang, Feng; Sadowski, Jerzy T.
Abstract : Charge transport at the interface of electrodes and ionic liquids is critical for the use of the latter as electrolytes. A room‐temperature ionic liquid, 1‐ethyl‐2, 3‐dimethylimidazolium bis(trifluoromethanesulfonyl)imide (EMMIM TFSI), is investigated in situ under applied bias voltage with a novel method using low‐energy electron and photoemission electron microscopy. Changes in photoelectron yield as a function of bias applied to electrodes provide a direct measure of the dynamics of ion reconfiguration and electrostatic responses of the EMMIM TFSI. Long‐range and correlated ionic reconfigurations that occur near the electrodes are found to be a function of temperature and thickness, which, in turn, relate to ionic mobility and different configurations for out‐of‐plane ordering near the electrode interfaces, with a critical transition in ion mobility for films thicker than three monolayers. Abstract : Reconfiguration of electric‐double‐layer ion ordering at electrified ionic liquid/solid interfaces involves complex restructuring of ions. Motion of oppositely charged ions during rearrangement is observed in real time using photoemission electron microscopy. This first step toward novel operando studies of ionic‐liquid electrolyte dynamics opens up experimental possibilities for correlating functional properties with local ionic measurements at electrolyte/electrode interfaces.